Exercise is feasible in patients receiving vasoactive medication in a cardiac surgical intensive care unit: A prospective observational study. Issue 3 (May 2020) - Boyd, Jemima; Paratz, Jennifer; Tronstad, Oystein; Caruana, Lawrence; Walsh, James
Abstract: Background: Patients may require vasoactive medication after cardiac surgery. The effect and safety profile of exercise on haemodynamic parameters in these patients is unclear. Objectives: The objective of this study was to measure the effect of upright positioning and low-level exercise on haemodynamic parameters in patients after cardiac surgery who were receiving vasoactive therapy and to determine the incidence of adverse events. Methods: This was a prospective, single-centre, observational study conducted in an adult intensive care unit of a tertiary, cardiothoracic university–affiliated hospital in Australia. The Flotrac-Vigileo™ system was used to measure haemodynamic changes, including cardiac output, cardiac index, and stroke volume. Normally distributed variables are presented as n (%) and mean (standard deviation), and non-normally distributed variables are presented as median [interquartile range]. Results: There were a total of 20 participants: 16 (80%) male, with a mean age of 65.9 (10.6) years. Upright positioning caused significant increases (p = 0.018) in the mean arterial pressure (MAP), with MAP readings increasing from baseline (supine), from 72.31 (11.91) mmHg to 77.44 (9.55) mmHg when back in supine. There were no clinically significant changes in cardiac output, heart rate, stroke volume, or cardiac index with upright positioning. The incidence of adverse events was low (5%). The adverse event was transient hypotension of low severity. Conclusions: Low-level exercise in patients after cardiac surgery receiving vasoactive medication was well tolerated with a low incidence of adverse events and led to significant increases in MAP. Upright positioning and low-level exercise appeared safe and feasible in this patient cohort.